2009
DOI: 10.1007/s12070-009-0020-x
|View full text |Cite
|
Sign up to set email alerts
|

Lipoid proteinosis of the larynx in siblings: exploring new modalities of treatment

Abstract: Lipoid proteinosis is a rare autosomal recessive disease inheritance with deposition of hyaline-like material at cutaneous and non-cutaneous sites. This is a report of two siblings presenting with typical cutaneous and laryngeal manifestations of lipoid proteinosis since birth who were treated successfully with placental extract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Hence, review of 51 cases of LP reported in India from 1969 to 2021 is done along with the present case [ Table 1a – c ]. [ 1 4 5 6 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 ] LP is more reported in patients in the age group of 11-20 (51%). More prevalence of LP is reported in males (70.6%).…”
Section: Review and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, review of 51 cases of LP reported in India from 1969 to 2021 is done along with the present case [ Table 1a – c ]. [ 1 4 5 6 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 ] LP is more reported in patients in the age group of 11-20 (51%). More prevalence of LP is reported in males (70.6%).…”
Section: Review and Discussionmentioning
confidence: 99%
“…On review of oral manifestations, 42 cases were found as shown in Table 1c . [ 1 4 5 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 25 26 27 28 29 30 31 32 33 34 35 37 38 39 42 43 44 ] The most common involved site is tongue with typical thick woody appearance followed by restricted tongue movements. In the present case, also similar findings were present.…”
Section: Review and Discussionmentioning
confidence: 99%